2019
DOI: 10.21276/ijcmr.2019.6.6.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity among Medical Students and its Correlation with Sleep Pattern and Duration

Abstract: Introduction: Overweight and obesity are defined as abnormal or excessive fat accumulation, which may impair health. Body mass index is a simple index of weight-for-height that is commonly used in classifying overweight and obesity in adult population and individuals. Sleep deficiency and sleep related disorders are colossal among the general population. Sleep deficiency and irregularity in sleep patterns has also been a common occurrence among doctors, as well as medical students for many years now. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…They had also found the association between sleep duration and obesity. 22 In contrast to our present study, a study conducted by Inam-ul-Haq et al at Islamabad medical college among 149 medical students, had found the statistically significant association between BMI categories and gender variables. (p=0.000).…”
Section: Resultscontrasting
confidence: 97%
“…They had also found the association between sleep duration and obesity. 22 In contrast to our present study, a study conducted by Inam-ul-Haq et al at Islamabad medical college among 149 medical students, had found the statistically significant association between BMI categories and gender variables. (p=0.000).…”
Section: Resultscontrasting
confidence: 97%
“…20 Study conducted in medical college from Srinagar India, they found that percentage of overall overweight and obesity was 19.4% and 4.4% among medical students . 21 Study conducted in Japanese university from 1979 to1991, was showed that the percentage of obesity is increasing progressively and among the boys of medical school. 22 A study from Greece on 989 third-year medical students showed that the 40% of boys and 23% of girls were obese.…”
Section: Resultsmentioning
confidence: 99%
“… 6 - 8 A similar study done in Jammu India which was found around 19% prevalence of overweight which was slightly lower than in our study. 9 …”
Section: Discussionmentioning
confidence: 99%